A preliminary evaluation of influence of body mass index on in vitro fertilization outcome in non-obese endometriosis patients - Eliana Garalejic; Biljana Arsic; Jovana Radakovic; Dragana Bojovic Jovic; Dragana Lekic; Biljana Macanovic; Ivan Soldatovic; Milan Perovic (BMC, 2017)
Abstract Background/aims Obese and overweight women experience a lower probability for pregnancy after IVF. However, despite the increasing prevalence of obesity, the large majority of infertile women are non-obese. One of the most common indications for IVF is endometriosis. Thought-provoking inverse correlation has been established between BMI and endometriosis. Lower BMI is a risk factor for development of endometriosis and a predictive factor for severe endometriosis. Since severe endometriosis carries lower reproductive chances, even after IVF, we preliminary tested a hypothesis that higher BMI among non-obese endometriosis patients improves IVF outcomes. Methods Preliminary retrospective observational cross-sectional study was performed in women with endometriosis as a sole infertility cause who underwent IVF. During analyzed period we performed 2782 IVF procedures. In order to achieve highly homogenous study sample and to eliminate almost all confound factors that could lead to bias, we implemented strict study criteria. The number of eligible subjects was 156 and they were divided into underweight, normal weight and overweight groups. Primary outcomes were number of retrieved oocytes, good quality oocytes, embryos, and the rates of biochemical, clinical and ongoing pregnancies. For group comparisons, we used parametric test, analysis of variance, and non-parametric tests (Kruskal-Wallis test, Chi-square test). Logistic regression and General linear model was used to assess correlation between BMI and dependent variables (outcome and stimulation duration) when adjusted for age. Results Endometriosis as a single infertility factor among IVF couples had prevalence of 5.61%. Underweight women accounted for 10.26%, normal weight 71.15% and overweight 18.59% of study population. Significant differences were not found in number of retrieved oocytes (p = 0.880), good quality oocytes (p = 0.476), obtained embryos (p = 0.706), and biochemical (p = 0.298), clinical (p = 0.770) and ongoing (p = 0.822) pregnancy rates between study groups. Conclusion Although preliminary results do not support our hypothesis, increase in BMI did not adversely affect the outcome of IVF in non-obese endometriosis patients, which is in contrast to literature data as regards general population of infertile women undergoing IVF. Prospective studies with large number of patients with endometriosis or prospective case-control studies should address these issues and provide more comprehensive counseling of infertile endometriosis patients regarding achievement of optimal BMI prior to IVF with the intention of achievement higher pregnancy rates.